PENATALAKSANAAN FISIOTERAPI PADA KASUS BELL’S PALSY SINISTRA DENGAN MODALITAS INFRARED, ELECTRICAL STIMULATION DAN MIRROR EXERCISE DI RS PINDAD KOTA BANDUNG - Silvyana Windi Astuti; Ika Rahman (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2021)
Bell's palsy is an acute weakness or paralysis of the facial peripheral nerves (facial nerve) on one side of the face. This condition causes the patient's inability to move half of his face consciously, on the affected side. To determine the implementation of Physiotherapy in increasing facial muscle strength, increasing the functional ability of facial muscles and reducing the thick feeling on the side of the face in the case of Bell's Palsy Sinistra by using Infrarred, Electrical Stimualtion modalities, and exercise therapy in the form of Mirror Exercise. After 6 times of therapy, the results of the assessment of increased muscle strength were obtained. Wrinkles forehead T1 : 1 to T6 : 3, Raises eyebrows T1 : 1 to T6 : 3, Closes eyes T1 : 1 to T6 : 3, Inflates nose and deflates T1 : 1 to T6 : 3 Smiles T1 : 1 To T6 : 3, scale up ugo fisch in resting position T1 : 6 becomes T6 : 14, frowns T1 : 3 becomes T6 : 7, closes eyes T1 : 9 becomes T6 : 21, smiles T1 : 9 becomes T1 : 21, whistles T1 : 3 becomes T6 : 3 . Infrared, Electrical stimulation and Mirror exercise can help increase facial muscle strength and improve the functional ability of facial muscles